Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The reality of the use of artificial intelligence applications by students of the Faculty of Graduate Education at King Abdul-Aziz University in the light of some variables Halima Hasan Alfageeh, Leena Ahmad Alfarani 2. Psychological well- being and its relationship to academic achievement at Sultan Qaboos University - Sultanate of Oman Hilal Salem Suleiman Al-Abri 3. Psychological Vitality and its relationship to Emotional Blackmail in a Sample of Husbands who are Emotionally Separated from their Wives Omar Sulaiman Al-Shelash 4. Post-Stroke Death Anxiety of a Sample of Stroke Patients at Bethlehem Arab Society for Rehabilitation and Surgery Mirna Mario Kharoufeh, Ola Ali Hussein 5. Health behavior and its relationship to existential anxiety among a sample of health sector students During the Corona pandemic Sarah Maflh Shaleh Alharthi 6. The impact of the psychological and social dimensions of digital transformation on the behavior of the individual and his family relations in the State of Kuwait Falah Saud Hasan Alrashidi 7. Attitudes of Arabic teachers towards distance learning in the schools within the green line in Palestine, and the obstacles that face them during any crisis Shaheen Jameel Shayeb, Maysa Mahmoud Bsharat, Khitam Mohamed Nathan Saqer 8. The Role of Strategic Vigilance as an Entrance to Achieving the Strategic Leadership in Saudi Universities Sylvia Ismail Mohammad Bani Hani